Statistical Population Genomics - Dutheil, Julien Y.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Humana, 2020)
This open access volume presents state-of-the-art inference methods in population genomics, focusing on data analysis based on rigorous statistical techniques. After introducing general concepts related to the biology of genomes and their evolution, the book covers state-of-the-art methods for the analysis of genomes in populations, including demography inference, population structure analysis and detection of selection, using both model-based inference and simulation procedures. Last but not least, it offers an overview of the current knowledge acquired by applying such methods to a large variety of eukaryotic organisms. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, pointers to the relevant literature, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Statistical Population Genomics aims to promote and ensure successful applications of population genomic methods to an increasing number of model systems and biological questions.
A Population Genomics Lexicon -- Processing and Analyzing Multiple Genomes Alignments with MafFilter -- Data Management and Summary Statistics with PLINK -- Exploring Population Structure with Admixture Models and Principal Components Analysis -- Detecting Positive Selection in Populations using Genetic Data -- polyDFE: Inferring the Distribution of Fitness Effects and Properties of Beneficial Mutations from Polymorphism Data -- MSMC and MSMC2: The Multiple Sequentially Markovian Coalescent.-Ancestral Population Genomics with Jocx, A Coalescent Hidden Markov Model -- Coalescent Simulation with sprime -- Inference of Ancestral Recombination Graphs using ARGweaver -- Population Genomics of Transitions to Selfing in Brassicaceae Model Systems -- Genomics of Long- and Short- Term Adaptation in Maize and Teosinte -- Neurospora from Natural Populations: Population Genomics Insights Into the Life History of a Model Microbial Eukaryote -- Population Genomics of Fungal Plant Pathogens and the Analyses of Rapidly Evolving Genome Compartments -- Population Genomics on the Fly: Recent Advances in Drosophila -- Genomic Access to the Diversity of Fishes -- Avian Population Genomics Taking Off: Latest Findings and Future Prospects -- Population Genomics of the House Mouse and the Brown Rat -- Population Genomics in the Great Apes.
Keywords: Bioinformatics; Genetics; Bioinformatics; Genetics and Genomics